Returning persons with SARS-CoV-2 to the field of play in professional golf: a risk assessment and risk reduction approach. Issue 2 (3rd May 2022) - Robinson, Patrick Gordon; Murray, Andrew; Close, Graeme; Glover, Danny; Du Plessis, Wimpie J
Abstract : Objectives: This pilot study aimed to see whether a risk assessment and risk reduction approach was a practical and feasible approach, as compared with standard isolation for fully vaccinated, asymptomatic persons positive for SARS-CoV-2. Methods: This prospective cohort study included all players and caddies participating in two large professional golf events from 7 to 20 February 2022 in South Africa. Fully vaccinated persons testing positive who were asymptomatic were subject to risk assessment and risk reduction measures to protect the integrity of the event. Asymptomatic individuals who could socially distance in outdoor areas were allowed to participate. Close contacts were subject to daily rapid antigen tests and asked to prioritise outdoor space. Results: The protocols put in place for the events were practical, feasible, and well accepted by event participants and staff during the study period. There was a total of 378 player-week episodes and 378 caddie-week episodes during the study period. Three persons tested positive while registered at events during the study period (0.4% of person episodes). The positive tests were returned from two players and one caddie, all of which were asymptomatic at the time of testing. There was one high-risk contact who consistently returned negative antigen tests. There was no evidence of transmission. Conclusions: The approach was practical and feasible. A risk assessment and risk reduction approach allowed fully vaccinated asymptomatic persons with SARS-CoV-2 to participate in golf, an outdoor sport where social distancing is possible, compared with standard isolation.